2014
DOI: 10.4103/2278-0203.132921
|View full text |Cite
|
Sign up to set email alerts
|

Facial profile preferences, self-awareness and perception among groups of people in the United Arab Emirates

Abstract: Objectives:The objective of this study is to assess the differences in facial profile preference among different layers of people in the United Arab Emirates. Facial profile self-awareness among the different groups was also evaluated.Materials and Methods:A total sample of 222 participants (mean [standard deviation] age = 25.71 [8.3] years, almost 80% of the participants were of Arab origin and 55% were males); consisting of 60 laypersons, 60 dental students, 60 general practitioners, 16 oral surgeons, and 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 19 publications
1
25
0
1
Order By: Relevance
“…This knowledge increases orthodontic tolerance of gingival display, unlike people from other professions. The present findings agree with those of Al Taki and Guidoum [ 27 ], who observed similar perceptions in facial aesthetic appearance between laypeople, dental students, general practitioners, oral surgeons, and orthodontists. In contrast, Zange et al [ 28 ] found that laypeople were more critical of aesthetics than orthodontists.…”
Section: Discussionsupporting
confidence: 93%
“…This knowledge increases orthodontic tolerance of gingival display, unlike people from other professions. The present findings agree with those of Al Taki and Guidoum [ 27 ], who observed similar perceptions in facial aesthetic appearance between laypeople, dental students, general practitioners, oral surgeons, and orthodontists. In contrast, Zange et al [ 28 ] found that laypeople were more critical of aesthetics than orthodontists.…”
Section: Discussionsupporting
confidence: 93%
“…4) that is dominant in relation to other facial features (nose, forehead, lips). Persons with Class III have a concave profile This pattern is considered the least aesthetic [2,24].…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily, the awareness among adults about the importance of occlusion has increased, and the number of adults seeking orthodontic treatment is rapidly growing. [ 3 ] Achieving a good bond to enamel can be accomplished by applying phosphoric acid to the enamel before bonding. [ 4 ] Etching of feldspathic ceramic surfaces with 9.6% hydrofluoric acid also causes micro retentions that can achieve a good bond.…”
Section: Introductionmentioning
confidence: 99%